ANTIOXIDANT ACTIVITIES FROM VARIOUS EXTRACTS OF DIFFERENT PARTS OF KELAKAI (STENOCHLAENA PALUSTRIS) GROWN IN CENTRAL KALIMANTAN - INDONESIA - Kusmardiyani, Siti; Novita, Grace; Fidrianny, Irda (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objectives: The aims of this research were to determine antioxidant activity from various extracts of different parts of kelakai (Stenochlaena palustris [Burm.f.] Bedd) using two antioxidant testing methods, which were 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP), and correlation of total phenolic contents (TPC), total flavonoid contents (TFC), and total carotenoid contents (TCC) with their inhibitory concentration 50% (IC 50 ) of DPPH and exhibitory concentration 50% (EC 50 ) of FRAP. Methods: Sample was extracted by reflux using different polarity solvents. The extracts were evaporated using vacuum rotary evaporator. Antioxidant activities were tested using DPPH and FRAP assays, determination of TPC, TFC, and TCC was carried out by ultraviolet-visible spectrophotometry, and correlation with their IC 50 of DPPH and EC 50 of FRAP capacities was analyzed by Pearson's method. Results: Ethanolic root extract of kelakai (S. palustris) had the lowest IC 50 of DPPH scavenging activity 0.8 Âµg/ml and the lowest EC of FRAP capacity 5.4 Âµg/ml. Ethanolic kelakai root extract demonstrated the highest phenolic content, ethyl acetate young leaves extract had the highest flavonoid content, and the highest carotenoid content was given by n-hexane root extract. There was significantly negative correlation between TPC in root extract of kelakai with their IC 50 of DPPH and EC 50 of FRAP. Conclusions: All different extracts of kelakai parts were categorized as very strong antioxidants by DPPH method. Phenolic compounds in kelakai root extract were the major contributor in antioxidant activities by DPPH and FRAP methods. DPPH and FRAP showed linear results in antioxidant activities of root kelakai extract. Keywords: Antioxidant, 2,2-diphenyl-1-picrylhydrazyl, Ferric reducing antioxidant power, Stenochlaena palustris, Young leaves, Old leaves, Root. 50